Creation and formation of information resources for children - Nadir, Ismayilov; Oruj, Guliyev (Technium Social Sciences Journal, 2022)
It should be noted that according to information obtained from written sources, the first book for children appeared in India in the 6th century BC. This didactic book tells about the moral and political conversations of a Brahmin in order to educate the ruler's son. The book, written in an entertaining style, consists of stories and fairy tales. In some sources, it is possible to find information that Confucius transcribed Chinese classics for children during that period. However, it is noted that this work has not been completed and the work remains unfinished. In the 600s AD, during the Anglo-Saxon period, monks and other scholars wrote a "textbook" for children. Aldhelm, Abbot of Malmesbury and Bishop of Sherborne, went down in history as the first person to write a textbook for children. His book De Septenario, de Metris, Enigmatibus ac Pedum Regulis contains a long essay on the meaning and use of the number seven in the Bible. Aldhelm assigned 1500 writing samples for children. He used question-and-answer form or wrote in poem form in all his manuals. Bede (673-735) used more imagination than Aldhelm. One of his most famous works was called "De Natura Rerum". Containing information on the natural sciences, history, astronomy and botany, this work has been used as an English textbook for more than three hundred years. Much of the content of Bede's works is a repetition of the scientific treatises of Plato, Aristotle, St. Augustine, and others [4, p.1].